Life-cycle consumption patterns at older ages in the US and the UK: Can medical expenditures explain the difference? - James Banks; Richard Blundell; Peter Levell; James P. Smith (Institute for Fiscal Studies (IFS), 2015)
In this paper we document significantly steeper declines in nondurable expenditures in the UK compared to the US, in spite of income paths being similar. We explore several possible causes, including different employment paths, housing ownership and expenses, levels and paths of health status, and out-of -pocket medical expenditures. Among all the potential explanations considered, we find that those to do with healthcare - differences in levels, age paths, and uncertainty in medical expenses - are the main factor accounting for the steeper declines in nondurable expenses in the US compared to the UK.
Keywords: D10; D11; D12; D14; D91; 330